Active labour market policies and short-time work arrangements: Evidence from a survey of Luxembourg firms - Konstantinos Efstathiou; Thomas Y. Mathä; Cindy Veiga; Ladislav Wintr (European Central Bank (ECB), 2017)
We analyse the use of active labour market policy (ALMP) measures and short-time work arrangements (STWAs) by Luxembourg firms during the years of economic and financial crisis (2008-09) and the subsequent European sovereign debt crisis (2010-13). About 34% of Luxembourg firms used ALMPs between 2008 and 2013. Economy-wide, use of ALMPs increased along both the extensive margin (more firms) and the intensive margin (more measures per firm). The likelihood that a firm hired with recourse to ALMPs is greater for large, domestically oriented, multiple establishment firms, firms facing strong demand, with concerns about labour cost pressures and unavailability of skilled labour. The crisis saw a surge in firms using STWAs. The likelihood of applying for STWAs increases with demand volatility, the share of workers with permanent contracts, export orientation and the inability to shift workers between establishments. Firms reported that 20-25% of jobs in STWAs were saved by this measure.
Keywords: C25; J63; J68; 330; Firms; survey; crisis; active labour market policy; short-time work arrangements